Symptomatic pleural lipoma - Tegeltija, Dragana Ratko; Bijelović, Milorad; Samardžija, Golub; Vasiljević, Tijana (Archive of Oncology, 2018)
Symptomatic pleural lipoma is an extremely rare clinical entity that can occur in all age groups and involve both sexes equally. The treatment can be done using video-assisted thoracoscopic surgery. We report a case of symptomatic pleural lipoma that was successfully removed using video-assisted thoracoscopic surgery.